PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII1 SMP NEGERI 3 PEKANBARU - Riska, Seha Dwi; Syofni, Syofni; Yuanita, Putri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a classroom action research that aims to improve the learning process and improve student learning outcomes through the application of the Discovery Learning model. This research was conducted in class VII1 of SMP Negeri 3 Pekanbaru in the 2019/2020 odd semester school year. The subjects of this study were 40 students consisting of 21 male students and 19 female students. The study was done in two cycles with each cycle consisting of three meetings and one repetition every day. The research instrument used was a learning device and data collection instrument. Learning tools consist of syllabus, lesson plan, and student work sheet. Data collection instruments consisted of observation sheets and learning outcomes tests. Based on data analysis of teacher and student activities, it appears that there is an improvement in the learning process after the Discovery Learning model is applied. The data obtained from the student mathematics learning achievement test shows that the competence of knowledge decreased the frequency of students at low and very low intervals from the base score (8 students) to the UH I score (4 students) and to the UH II score (2 students) as well as an increase in the frequency of students at high and very high intervals base score (21 students) to UH I score (34 students) and to UH II score (37 students). The competence of skills decreased the frequency of students at low and very low intervals from the base score (8 students) to the UH I score (6 students) and to the UH II score (4 students) as well as an increase in the frequency of students at high and very high intervals base score (21 students) to UH I score (23 students) and to UH II score (30 students).This study results indicate that the implementation of the Discovery Learning model can improve the learning process and improve mathematics learning outcomes of grade VII1 students of SMP Negeri 3 Pekanbaru.Key Words : Classroom Action Research, Discovery Learning Model, Mathematical Learning Outcomes